Does renting luxury make me shine? The mediating role of perceived signals. Issue 8 (30th April 2022) - Gong, Yanping; Zhang, Qin; Zhang, Jifei
Abstract: Whether rented luxury creates symbolic meaning for consumers who cannot afford it, thus, providing them with an effective way to construct their identity, similar to owned luxury, and strengthen their willingness to rent. Drawing on implicit self‐theories, we find that compared with entity theorists, incremental theorists have lower willingness to rent luxury products (Studied 1, 2, and 3), but they do not exhibit significant differences in self‐brand connection (Studied 2 and 3). We show that incremental theorists (vs. entity theorists) perceive more authentic signal than symbolic signal regarding their inability to afford luxury goods when using rented luxury products (Study 3). Neither in ownership‐based luxury consumption (Study 4, where there is no authentic signal), nor in access‐based nonluxury consumption (Study 5, where there is no symbolic signal), consumers with different implicit beliefs no longer differentiate in buying/renting intentions. Our work suggests that not all consumers who desire unaffordable luxuries are willing to rent them. Therefore, managers should consider how to reduce the negative impacts of authentic signals on incremental theorists' renting intentions.